Nadezhda Chemezova at 80 m of Her Record 200 m Swim at the 1998 Goodwill Games in New York - Rushall, B. S.
Video pictures (13 frames) and the appropriate technical/ biomechanical explanations for Nadezhda Chemezova at 80 m of her record 200 m swim at the 1998 Goodwill Games in New York. Nadezhda Chemezova's stroke exhibits a classic two-beat kicking action. To substitute for four beats the magnitude of the kick is greater than most other swimmers. It starts with the foot out of the water and finishes quite deep, well below the cross-sectional profile of the swimmer's torso. Her stroke is long but asymmetrical. The left arm pulls with the elbow-up but the right arm, while positioning the hand/forearm and possibly upper arm surfaces, does not propel through as much distance. The right elbow-up position allows propulsion to start further in front of the swimmer and positions the adductor muscles with greater stretch than occurs with the left arm. One is set to wondering if the swimmer would gain any performance improvement by attempting an elbow-up action with the left arm.